Towards conflict or cooperation? The Ukraine crisis and EU-Russia relations. Issue 3 (2nd July 2016) - Nitoiu, Cristian
Abstract: The Ukraine crisis and Russia's contribution to it have raised numerous concerns regarding the possible emergence of a new 'Cold War' in Europe. At the same time, Ukraine's popular choice and enthusiasm for European integration expressed clearly on the streets of Kyiv seem to have caused Russia to adopt a (neo)revisionist attitude. In this context, relations between Russia and the EU (and the West for that matter) have been limited, frozen and directed on path towards conflict. This article analyses how the traditional dichotomy between conflict and cooperation in EU–Russia relations was replaced by conflict in the context of the Ukraine crisis. The article contends that the breakdown of the symbolic and peaceful cohabitation between the EU and Russia has been influenced by the fact that both actors have chosen to ignore key tensions that characterized their post-Cold War interactions. The article identifies three such tensions: the first emphasizes divisions between EU member states and their impact on coagulating a common EU approach towards Russia; the second (geopolitical) tension highlights the almost mutually exclusive way in which the EU and Russia's security interests have developed in the post-Soviet space; finally, the third contends that a clash of values and worldviews between the EU and Russia makes conflict virtually unavoidable.